Delphic and Odyssean monetary policy shocks: Evidence from the euro area - Philippe Andrade; Filippo Ferroni (Federal Reserve Bank of Chicago, 2018)
We use financial intraday data to identify monetary policy surprises in the euro area. We find that monetary policy statements and press conferences after European Central Bank (ECB) Governing Council meetings convey information that moves the yield curve far out. Moreover, the nature of the information revealed in a narrow window around these statements and press conferences evolved over time. Until 2013, unexpected variations in future interest rates were positively correlated with the changes in market-based measure of inflation expectations consistent with news on future macroeconomic conditions. That negative correlation disappeared roughly when forward guidance on future rates started to be given by the Governing Council. We use conditions on the joint reaction of expected interest rates and inflation rates to disentangle the two types of monetary policy shocks (i.e. the Delphic and Odyssean monetary policy surprise). A surprise that lowers future interest rates does not engineer a boom. A surprise that lowers future interest rates because it signals future accommodation does.
Keywords: C10; E52; E32; 330; signaling; forward guidance; high frequency data; VAR with instrumented proxy; euro area